KEPATUHAN TERHADAP PERATURAN PERUNDANGAN PEMBANGUNAN PERKEBUNAN BERKELANJUTAN: KEPATUHAN TERHADAP PERATURAN PERUNDANGAN PEMBANGUNAN PERKEBUNAN BERKELANJUTAN - Darmono (ECO-BUILD, 2022)
Compliance with Laws and Regulations on Sustainable Plantation Development. By Darmono, University of Muhammadiyah Berau. The research objectives are to identify various laws and regulations regarding sustainable plantation development; identify various problems faced by business actors/planters in implementing the applicable laws and regulations; collect and select input suggestions/opinions on the most effective method/pattern/system for submitting laws and regulations; and seek input on the parties most responsible for the implementation of laws and regulations. The results of the discussion can be concluded that, there are three aspects that must be formulated in order to strengthen the ISPO compliance system. First, the aspect of legal substance. The ISPO system arrangement should be upgraded from a ministerial regulation of agriculture to a presidential regulation. This presidential regulation is expected to become a stronger legal umbrella in the implementation of the ISPO system. Second, the aspect of the legal apparatus. The institutional mechanism for implementing ISPO certification must be refined and strengthened. Third, the aspect of legal culture. There must be a common understanding related to the definition and concept of sustainability in the management and development of Indonesian palm oil